Comparison of Occlusal Parameters between Open Bite and Nonopen Bite Patients Using the T-Scan III System: A Pilot Study - Chaikla, Katika; Pumklin, Jittima; Piyapattamin, Thosapol (European Journal of Dentistry, 2022)
Objective To evaluate and compare the first tooth contact region, occlusion time, time to generate total force, and force distribution between open bite (OB) and non-OB (NOB) patients at the maximum intercuspation position using the T-Scan III system.Materials and Methods Sixteen patients were divided into the OB and NOB groups (n = 8 for each group). The T-Scan III system was used to evaluate the first tooth contact region, occlusion time, time to generate total force, and force distribution.Statistical Analysis The mean patient age, overjet, overbite, occlusion time, and time to generate total force were compared between the groups by independent samples t-test. Relative force distributions between groups and among regions were compared by the Mann–Whitney U- and Kruskal–Wallis H-tests, respectively. A probability value of less than 5% (p < 0.05) was considered significant.Results Differences in the first tooth contact region between groups were observed. The molar region was the first tooth contact region in the OB group, while first tooth contact was observed in all regions in the NOB group. Neither the occlusion time nor the time to generate total force was significantly different between the groups (p > 0.05). The highest force distributions were observed in the molar regions in both groups. Significant intragroup differences were found among all regions (p < 0.05), except between the anterior and premolar regions in the NOB group (p = 0.317). Intergroup differences in the force distributions in the anterior (p = 0.000), premolar (p = 0.038), and molar (p = 0.007) regions were significant.Conclusion Unlike in the NOB group, in which first tooth contact occurred in every region, in the OB group, first tooth contact occurred only in the molar region. Compared with those in the NOB group, the force distributions in the OB group were approximately 1.5 times higher in the molar region but were significantly lower in the anterior and premolar regions.
Keywords: first tooth contact; occlusal force distribution; occlusion time; open bite; T-Scan